Predicted Effects and Cost-Effectiveness of Wheat Flour Fortification for Reducing Micronutrient Deficiencies, Maternal Anemia, and Neural Tube Defects in Yaoundé and Douala, Cameroon. Issue 4 (December 2021) - Noshirvan, Arram; Wu, Brenda; Luo, Hanqi; Kagin, Justin; Vosti, Stephen A.; Ndjebayi, Alex; Assiene, Jules Guintang; Teta, Ismael; Nankap, Martin; Engle-Stone, Reina
Background: Policy makers aiming to reduce micronutrient deficiencies (MNDs) and their health effects must choose among alternative definitions of impact when evaluating cost-effectiveness. Objective: Estimate the cost-effectiveness of a mandatory wheat flour fortification program for reducing cases of MNDs (iron, zinc, folate, vitamin B12), anemia and neural tube defects (NTDs) averted, and disability-adjusted life years (DALYs) averted in urban Cameroon. Methods: A 13-year predictive model was developed, including a 3-year start-up period and 10 years of program activity. Costs were estimated using historical program budgets. Effects were calculated based on observed changes in prevalence of MND and anemia 1 year postfortification and predicted reductions in NTDs based on NTD burden and wheat flour intake. Total DALYs averted were estimated for anemia and NTDs. Results: The program cost ∼$2.4 million over 13 years and averted an estimated ∼95 000 cases of maternal anemia and ∼83 500 cases of iron deficiency among children after 1 year. Cost/case-year averted for MNDs ranged from $0.50 for low plasma folate to $3.30 for iron deficiency and was $2.20 for maternal anemia. The program was predicted to avert 1600 cases of NTDs over 10 years at ∼$1500 per case averted. Estimated cost/DALY averted was $50 for NTDs and $115 for anemia. Conclusions: In Cameroon, cost-effectiveness of wheat flour fortification varied by the measure of impact employed, but was classified as "very cost-effective" for all outcomes using World Health Organization criteria. Policy makers and their advisors must determine how best to use information on program costs and benefits to inform their decisions.